Male circumcision as HIV/Aids prevention strategy in South Africa - Tsimane, Salathiel (2014)
M.A. (Public Management and Governance) === This study starts with an introduction and background, and this is followed by a statement of the research problem, research rationale, research objectives, research design, research methodology and the data collection methods. A list of acronyms will be provided, as well as an overview of chapters, conclusions, and acknowledgements. “Around 5.7 million in 2009 had contracted HIV and AIDS and in the preceding year 250,000 South Africans died due to HIV/AIDS related diseases. All age categories and gender are prone to contracting the disease and the resultant loss of life has had a devastating effect on the workforce. Death due to this disease has caused loss of income and family disintegration” (Sottile 2013:2). In 2010, some 280,000 South Africans died of HIV/AIDS. In the decade up to 2010, between 42% and 47% of all deaths among South Africans were HIV/AIDS-related deaths (Sottile 2013:2). Mlambo et al (2011:1) further say that “The Human Sciences Research Council estimates that 10.9% of all South Africans have HIV/AIDS. Additionally, the Central Intelligence Agency estimates that 310,000 individuals died in South Africa from HIV/AIDS in the year 2009”. A study in 2003 made a comparison on two scenarios, an HIV/AIDS scenario and a no-HIV/AIDS scenario and this was based on the annual growth rates between 2002 and 2015. The finding was that “real growth in GDP would be 0.6% lower than if there were no HIV/AIDS, but per-capita growth in GDP would be 0.9% higher. Growth in population would have been 1.5% lower, and growth of the labour force would be 1.2% lower, but the unemployment rate would be 0.9% lower as well” (Avert.Org 2010:2). Different HIV/AIDS prevention strategies are being implemented in South Africa. The focus in this study is on male medical circumcision (hereafter MMC), which is the removal of all or part of the foreskin on the penis. It can either be performed surgically in hospitals or at initiation schools. Initiation schools perform the procedure as a traditional rite of passage from boyhood to manhood, and this is referred to as traditional male circumcision (TMC). This practice has up till now been performed purely for traditional or religious purposes, but it can no longer be viewed only as such. It should, instead, also be seen as a measure to curb the spread of the HIV/AIDS pandemic. A number of observational studies (which will be referenced later) found that circumcised men had smaller chances of contracting HIV infection compared with uncircumcised men...